Gdy Rylski spotyka się z Nabokovem… ("Dziewczynka z hotelu Excelsior" i fenomen nimfetki) - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2014)
Eustachy Rylski’s story – A Little Girl from the Hotel ‘Excelsior’ – can be read as an example of psychological prose with a distinctive existential outline – as a literary study of alienation, aging and gradual loss of connections with life. There is a temptation to see in it a work that, in a discreet way, refers to the outstanding achievements of Polish prose (such as Iwaszkiewicz’s Tatarak) and world prose (such as Vladimir Nabokov’s Lolita, Thomas Mann’s Death in Venice, Truman Capote’s Miriam and even some works of Edgar Allan Poe). The specific artistic character of Rylski’s work is based on the processing of various ideas linked with the illusion of the femme fatale (including the Young Poland idea of the women-animal), nymphet figures and the ‘odd child’ and introduce them into the caricatured scenery of the Polish People’s Republic. In this broad intertextual context, one can see in Inte – this ‘beautiful temptress’ but also an ordinary ‘little whore’ – something more than a literary manifestationof misogyny, a contemporary crisis of masculinity or a battle of the sexes